2020
DOI: 10.3390/children7100162
|View full text |Cite
|
Sign up to set email alerts
|

Successful Hematopoietic Stem Cell Transplantation from a Matched Related Donor with Beta-Thalassemia Minor for Severe Aplastic Anemia

Abstract: The first-line treatment for severe aplastic anemia (SAA) patients is hematopoietic stem cell transplantation (HSCT), with full-matched related donors considered the most suitable. We report a case of SAA in which the patient successfully underwent HSCT from a donor with β-thalassemia minor. The patient in this case underwent HSCT from a human leukocyte antigen (HLA)-matched younger brother with β-thalassemia minor. A 7-year-old girl was referred to our facility following a 6-month history of easy bruising and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Mi YJ et al reported a rare case in which allo-HSCT for a 7-year-old severe aplastic anemia patient from a MSD with mild b-thalassemia was performed successful. In this case, the engraftment of erythrocytes was evident, good performance status has been observed throughout the 5 years after HSCT and the PBSCs mobilized by G-CSF were sufficient (11). Li K et al also reported that for the efficiency of mobilization of PBCSs in patients with thalassemia, there were no significant differences in the CD34+ cell subsets and lymphocyte subsets after G-CSF administration when compared with those in healthy donors (12).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Mi YJ et al reported a rare case in which allo-HSCT for a 7-year-old severe aplastic anemia patient from a MSD with mild b-thalassemia was performed successful. In this case, the engraftment of erythrocytes was evident, good performance status has been observed throughout the 5 years after HSCT and the PBSCs mobilized by G-CSF were sufficient (11). Li K et al also reported that for the efficiency of mobilization of PBCSs in patients with thalassemia, there were no significant differences in the CD34+ cell subsets and lymphocyte subsets after G-CSF administration when compared with those in healthy donors (12).…”
Section: Discussionmentioning
confidence: 70%
“…reported a rare case in which allo-HSCT for a 7-year-old severe aplastic anemia patient from a MSD with mild β-thalassemia was performed successful. In this case, the engraftment of erythrocytes was evident, good performance status has been observed throughout the 5 years after HSCT and the PBSCs mobilized by G-CSF were sufficient ( 11 ). Li K et al.…”
Section: Discussionmentioning
confidence: 83%
“…However, advances in medical science have resulted in innovative treatment strategies. Hematopoietic stem cell transplantation from a matched sibling donor has been considered the gold standard for treatment, offering a potential cure ( 8 , 9 ). However, the availability of suitable donors is limited, and the procedure carries risks of complications ( 3 ).…”
Section: Introductionmentioning
confidence: 99%